1998
DOI: 10.1063/1.476429
|View full text |Cite
|
Sign up to set email alerts
|

On the simulation of vapor–liquid equilibria for alkanes

Abstract: A Monte Carlo simulation study has been conducted to assess the ability of recently proposed force fields to predict orthobaric densities, second virial coefficients, and P-V-T data for short and long alkanes. A new, modified force field is proposed that provides good agreement with experimental phase equilibrium and second virial coefficient data over wide ranges of temperature and chain length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
388
1
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(412 citation statements)
references
References 29 publications
11
388
1
12
Order By: Relevance
“…In Table 1, it seems counterintuitive that a methyl group should be smaller than a methylene group, but this is actually consistent with other force fields designed for simulating n-alkanes. 67,72 Second, adjacent united atoms within the same chain overlap by virtue of specification of the equilibrium bond lengths. It has been shown that these are essential requirements in order for a united atom model to reproduce the maxima in critical pressure and density as a function of chain length.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1, it seems counterintuitive that a methyl group should be smaller than a methylene group, but this is actually consistent with other force fields designed for simulating n-alkanes. 67,72 Second, adjacent united atoms within the same chain overlap by virtue of specification of the equilibrium bond lengths. It has been shown that these are essential requirements in order for a united atom model to reproduce the maxima in critical pressure and density as a function of chain length.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…Bond stretching and bending are described by harmonic potentials 67,68 Figure 1. Equation of state of the energy landscape for n-hexane.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…For the hydrocarbons, special force fields, both for united-atom and allatom models, have been developed that give an accurate description of the vapor-liquid coexistence curve over a wide range of conditions. 57,78,[80][81][82][83][84][85][86] Figure 12 gives a typical illustration of the accuracy that can be obtained with these types of models.…”
Section: Adsorbate-adsorbate Interactionsmentioning
confidence: 99%
“…Thus, the number of Van der Waals interactions sites for a given alkane equals its number of carbon atoms and the bead center is located at the carbon atom positions. Other successful UA potentials are the NERD potential [25] proposed by Nath et al in 1998 or the TraPPE family models [26] developed by Martin and Siepmann.…”
Section: Available Force Fieldsmentioning
confidence: 99%